PEDAGOGIK CONDITIONS FOR DEVELOPING STUDENTS’ COGNITIVE INTEREST IN PHYSICS THROUGH MODERN EDUCATIONAL TECHNOLOGIES - Asamatdinova, Ulbosin Maxmudovna (SCIENCE and SOCIETY, 2026)
This article examines the application of interactive technologies in teaching physics to students with disabilities within the framework of inclusive education. The relevance of using digital educational resources, virtual laboratories, multimedia tools, and adaptive learning systems is substantiated. The study analyzes their impact on learning outcomes, cognitive engagement, and student motivation. Practical examples of implementing interactive technologies in teaching various physics topics are presented. The main challenges associated with the integration of these technologies, including technical, methodological, and organizational issues, are identified, and possible solutions are proposed. The study concludes that interactive technologies are an effective means of improving the accessibility and quality of physics education for students with special educational needs.
Keywords: interactive technologies; physics education; inclusive education; students with disabilities; virtual laboratories; digital learning resources; adaptive learning